Training on the Utilization of Leather Waste from Bag Craft Industries into Keychain Products - Endang Suprihatin; Asfarina Hidayah; Ananda Fathurahman Bintang Pradana (Jurnal Pengabdian Masyarakat Bhinneka, 2026)
The leather bag craft industry generates waste that is often not fully utilized. This waste has the potential to pollute the environment if not properly managed. This community service activity aims to develop innovative ways to utilize leather waste into keychains that have economic value. The activity covers material selection, design, production processes, and product evaluation. The results of the activity include training and hands-on practice for women’s organization members, resulting in several products such as keychains with various motiv including circles, squares, and other shapes. The outcomes demonstrate that leather waste can be processed into attractive, durable keychains that are in demand by consumers. In addition to reducing waste, this innovation has the potential to increase the income of women in the community as well as local artisans